CuO and Ag2O/CuO Catalyzed Oxidation of Aldehydes to the Corresponding Carboxylic Acids by Molecular Oxygen - Yaowu Sha; Daxin Shi; Qingyong Tian (Molecules, 2008)
Furfural was oxidized to furoic acid by molecular oxygen under catalysis by 150nm-sized Ag2O/CuO (92%) or simply CuO (86.6%). When 30 nm-size catalyst was used,the main product was a furfural Diels-Alder adduct. Detailed reaction conditions andregeneration of catalysts were investigated. Under optimal conditions, a series of aromaticand aliphatic aldehydes were oxidized to the corresponding acids in good yields.